Prezident respubliki Koreia Kim En Sam v Moskve . Prezident respubliki Koreia Kim En Sam v Moskve . President of the Republic of Korea Kim Yong-Sam in Moscow . Президент республики Корея Ким Ён Сам в Москве - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Report on the visit of Korean President to Moscow. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Kim, Young Sam (President of the Republic of Korea) Репортаж о визите президента Кореи в Москву. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Ким, Ён-Сам (Президент республики Корея)